Antioxidant enzyme responses in different wheat species infested with the corn leaf aphid, Rhopalosiphum maidis Fitch - Kumari, Pritam; Jasrotia, Poonam; Maanju, Sunny; Sareen, Sindhu; Kumar, Dinesh (Frontiers in Plant Science, 2025)
Wheat (Triticum aestivum L.) is a staple crop worldwide, but it remains vulnerable to the corn leaf aphid (Rhopalosiphum maidis Fitch), a major pest that causes both direct yield losses and indirect damage through disease transmission. To elucidate biochemical mechanisms underlying resistance, 65 wild and synthetic wheat genotypes were evaluated under aphid-infested and uninfested conditions. Aphid nymphal mortality varied significantly across genotypes, with amphidiploid and Aegilops kotschyi showing the highest resistance, while synthetic wheat lines exhibited moderate aphid mortality. Biochemical assays revealed consistent induction of antioxidant enzymes, viz., catalase (CAT), ascorbate peroxidase (APX), peroxidase (POX), and glutathione reductase (GR), across all genotypes upon infestation. Synthetic wheat displayed the highest enzymatic activities, indicating robust oxidative stress tolerance, whereas amphidiploid wheat maintained lower enzyme activity but exerted strong aphid mortality, suggesting reliance on non-enzymatic or constitutive defenses. Additionally, phenylalanine ammonia-lyase (PAL) and polyphenol oxidase (PPO), key enzymes in the phenylpropanoid pathway, were strongly upregulated in synthetic wheat and Ae. kotschyi, highlighting their role in secondary metabolite-mediated defense. These findings demonstrate that wheat resistance to R. maidis is multifaceted, involving both antioxidant enzyme regulation and phenylpropanoid metabolism. Genotypic differences underscore the potential of wild relatives and synthetic wheats as valuable genetic resources for breeding durable, eco-friendly aphid-resistant wheat cultivars. Integrating these biochemical insights into breeding programs can accelerate the development of resistant cultivars, reducing pesticide use and strengthening food security under pest and climate challenges.